From 8d3e9fdc208e31d714444b87ae9e01ae9e923b5d Mon Sep 17 00:00:00 2001 From: Leonardo de Moura Date: Fri, 31 Oct 2014 08:29:46 -0700 Subject: [PATCH] refactor(library/data/nat/basic): remove unnecessary `{}` --- library/data/nat/basic.lean | 28 ++++++++++++++-------------- 1 file changed, 14 insertions(+), 14 deletions(-) diff --git a/library/data/nat/basic.lean b/library/data/nat/basic.lean index 993c92337..801569b01 100644 --- a/library/data/nat/basic.lean +++ b/library/data/nat/basic.lean @@ -53,7 +53,7 @@ have H2 : true = false, from let f := (nat.rec false (fun a b, true)) in calc true = f (succ n) : rfl - ... = f 0 : {H} + ... = f 0 : H ... = false : rfl, absurd H2 true_ne_false @@ -88,7 +88,7 @@ or.elim (zero_or_succ_pred n) theorem succ.inj {n m : ℕ} (H : succ n = succ m) : n = m := calc n = pred (succ n) : pred.succ - ... = pred (succ m) : {H} + ... = pred (succ m) : H ... = m : pred.succ theorem succ.ne_self {n : ℕ} : succ n ≠ n := @@ -155,14 +155,14 @@ induction_on n (take m IH, show 0 + succ m = succ m, from calc 0 + succ m = succ (0 + m) : add.succ_right - ... = succ m : {IH}) + ... = succ m : IH) theorem add.succ_left (n m : ℕ) : (succ n) + m = succ (n + m) := induction_on m (!add.zero_right ▸ !add.zero_right) (take k IH, calc succ n + succ k = succ (succ n + k) : add.succ_right - ... = succ (succ (n + k)) : {IH} + ... = succ (succ (n + k)) : IH ... = succ (n + succ k) : add.succ_right) theorem add.comm (n m : ℕ) : n + m = m + n := @@ -170,7 +170,7 @@ induction_on m (!add.zero_right ⬝ !add.zero_left⁻¹) (take k IH, calc n + succ k = succ (n+k) : add.succ_right - ... = succ (k + n) : {IH} + ... = succ (k + n) : IH ... = succ k + n : add.succ_left) theorem add.move_succ (n m : ℕ) : succ n + m = n + succ m := @@ -185,15 +185,15 @@ induction_on k (take l IH, calc (n + m) + succ l = succ ((n + m) + l) : add.succ_right - ... = succ (n + (m + l)) : {IH} + ... = succ (n + (m + l)) : IH ... = n + succ (m + l) : add.succ_right ... = n + (m + succ l) : add.succ_right) theorem add.left_comm (n m k : ℕ) : n + (m + k) = m + (n + k) := -left_comm @add.comm @add.assoc n m k +left_comm add.comm add.assoc n m k theorem add.right_comm (n m k : ℕ) : n + m + k = n + k + m := -right_comm @add.comm @add.assoc n m k +right_comm add.comm add.assoc n m k -- ### cancelation @@ -268,7 +268,7 @@ induction_on m (!mul.zero_right ⬝ !mul.zero_right⁻¹ ⬝ !add.zero_right⁻¹) (take k IH, calc succ n * succ k = (succ n * k) + succ n : mul.succ_right - ... = (n * k) + k + succ n : {IH} + ... = (n * k) + k + succ n : IH ... = (n * k) + (k + succ n) : add.assoc ... = (n * k) + (n + succ k) : add.comm_succ ... = (n * k) + n + succ k : add.assoc @@ -279,7 +279,7 @@ induction_on m (!mul.zero_right ⬝ !mul.zero_left⁻¹) (take k IH, calc n * succ k = n * k + n : mul.succ_right - ... = k * n + n : {IH} + ... = k * n + n : IH ... = (succ k) * n : mul.succ_left) theorem mul.distr_right (n m k : ℕ) : (n + m) * k = n * k + m * k := @@ -291,7 +291,7 @@ induction_on k ... = n * 0 + m * 0 : mul.zero_right) (take l IH, calc (n + m) * succ l = (n + m) * l + (n + m) : mul.succ_right - ... = n * l + m * l + (n + m) : {IH} + ... = n * l + m * l + (n + m) : IH ... = n * l + m * l + n + m : add.assoc ... = n * l + n + m * l + m : add.right_comm ... = n * l + n + (m * l + m) : add.assoc @@ -314,7 +314,7 @@ induction_on k (take l IH, calc (n * m) * succ l = (n * m) * l + n * m : mul.succ_right - ... = n * (m * l) + n * m : {IH} + ... = n * (m * l) + n * m : IH ... = n * (m * l + m) : mul.distr_left ... = n * (m * succ l) : mul.succ_right) @@ -346,8 +346,8 @@ discriminate assume (Hl : m = succ l), have Heq : succ (k * succ l + l) = n * m, from (calc - n * m = n * succ l : {Hl} - ... = succ k * succ l : {Hk} + n * m = n * succ l : Hl + ... = succ k * succ l : Hk ... = k * succ l + succ l : mul.succ_left ... = succ (k * succ l + l) : add.succ_right)⁻¹, absurd (Heq ⬝ H) !succ_ne_zero))